Abdominal Wall Closure in Emergency Laparotomy: Management and Outcome in Omdurman Teaching Hospital (Global Journal of Medical Research, 2014)
Background: T h e incisions those applied in approaching those operations , were vertical anterior abdominal incisions (midline or paramedian), and the way these incisions were closed, it was either mass or layered abdominal wall closure and types of suture materials used in the closure, non - absorbable/absorbable, monofilament (Nylon)/ polyfilament (Vicryl). Objectives: T o stu dy a series of patients those who underwent vertical incisions, either midline or paramedian and how t hey were closed, mass or layered closure and suture materials used inclosing the abdomen and the outcome. Patients and methods: This study is an observational prospective analytical hospital based study. Conducted at Omdurman Teaching Hospital, Sudan, over one year duration from 2012 Sep to 2013 Sep. Included were patients who underwent vertical anterior abdominal incisions (midline or paramedian) for emergency laparotomy, Non probability sampling including patients consecutively. Questionnaires were used a nd the variables were; demographical patient data, indications for laparotomy, suture materials used in these closures, technique of closing the fascial layer and skin and the outcome. Patient consent and ethical clearance were obtained in advance. Data wa s analyzed using SPSS version 20 and the P value was considered significant if ã´€ 0.05. Patients and methods: R e sults: 114 ( 91.9% ) patients underwent midline incisions and 10(8.1%) patients were paramedian incision. Mass closure were111 (89.5%) and layered were13 (10.5%) patients, types of suture materials used in the closure technique were non - absorbable polyamide (Nylon) 103(83.1%). Delayed absorbable polygactin 910 (Vicryl) 21 (19.9%). Sutures size used 2# (106) Nylon 90 (87.4%) Vicryl 16 (76.2%), 1# (17) Nylon 12 (11.7%) - vicryl 5(23.8%) and only one 0# (0.8%). Length of hospital stay 5days and less 55 (44.4%) patients, >5 - 10 days 52 (41.9%) patients and >10 days were 16 (13.7%) p
Keywords: laparotomy incision closure; suture material; closure technique